The Evolution of Kicking Techniques in Taekwondo (Revista de Artes Marciales Asiáticas, 2012)
The purpose of the study is to explain the evolution of kicking techniques of taekwondo and to provide a historical time frame for this process. This study analyzes early karate and taekwondo literature, including diverse and varied Korean sources. In addition, some interviews were conducted with relevant persons of the period researched. Taekwondo and karate training and techniques had been very similar until the 1960s. However, taekwondo diverged from karate techniques with the introduction of full-contact competitions during the 1960s.